2014
DOI: 10.11118/actaun201058020147
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pig manure fermented by larvae of house flies on the yield parameters of sunflowers (Helianthus annus L.)

Abstract: The effect of fermented pig manure processed on a bed of wooden shavings and fermented for seven days by larvae of house flies on the yield parameters of sunflowers have been investigated on Haplic Luvisol in the pot trial realized in vegetative cage placed on the territory of SAU in Nitra. The experiment consisted of six treatments (0, NPK, Manure1, Manure2, Manure3, Veget). Treatments 0, NPK, and Veget were compared with the treatments Manure1, Manure2, and Manure3, i.e. with fermented manure applied at dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 4 publications
0
11
2
1
Order By: Relevance
“…This is confirmed by the correlation coefficients between the thickness of the stalk and the plant heights measured in the individual phenological growth stages (Table 5). This find does not correspond with the knowledge of Kováčik et al (2010), who found Table 6, is obvious that the application of vermicompost, either alone or together with mineral fertilizer, had a significant influence on phytomass yield taken in growth stage BBCH 16 and on the total chlorophyll content (Chl a + b).…”
Section: Resultsmentioning
confidence: 47%
“…This is confirmed by the correlation coefficients between the thickness of the stalk and the plant heights measured in the individual phenological growth stages (Table 5). This find does not correspond with the knowledge of Kováčik et al (2010), who found Table 6, is obvious that the application of vermicompost, either alone or together with mineral fertilizer, had a significant influence on phytomass yield taken in growth stage BBCH 16 and on the total chlorophyll content (Chl a + b).…”
Section: Resultsmentioning
confidence: 47%
“…The frass application has positively impacted plant growth [55]. Focusing on frass quality in detail, concluded that frass nutrient levels should be high enough for a fertilizing effect, but there is still a lack of understanding of how frass practically affects soil fertility and plant growth [48].…”
Section: Uses Of Black Soldier Fly Frass Bio-fertilizer In Vegetable Crop Production and Soil Amendmentmentioning
confidence: 99%
“…However, when compared to animal proteins, plant feedstuffs have lower protein content, unbalanced essential amino acid profiles, lower palatability, the presence of antinutrients (e.g. phytates, gossypol, tannins and lectin) and competition with other food‐feed industry sectors (Gatlin et al, ; Glencross, Booth, & Allan, ; Kováˇcik, Kozánek, Takáˇc, Galliková, & Varga, ).…”
Section: Introductionmentioning
confidence: 99%